PERKEMBANGAN TEKNOLOGI PEMBELAJARAN DAN PENGARUHNYA TERHADAP PERKEMBANGAN PESERTA DIDIK - Rusydi Ananda (Hijri, 2017)
The advancement of technology is not only a matter of science and knowledge but has had an impact in education. The perceived development of technology by the utilization of technology in implementing the lesson so that it makes the technology lesson of the teacher's learning and to facilitate the students to learn quickly. The developmental product of the teaching-learning that teachers can be done by packing various materials and learning resources in the sports manufacturing technology or to be a medium lesson. With the absence of media technology that can be utilized to be a learning media can give the impact of learning of students.